Terpenoidal and steroidal constituents of Vernonia patula (Dry.) Merr. (Fam. Compositae) - Herrera, Celia Lopez 1935-
Four terpenes and one sterol were isolated from the whole plant of Vernonia patula (Dry.) Merr. Two of the terpenes, designated as V-1 and V-2 were identified as α-amyrin acetate and α-amyrin respectively and the sterol designated as V-3 was identified as β-sitosterol. The other two terpenes isolated were not identified. From their IR spectra, V-4, m.p. 75-77(degrees C) could be a terpene ester while V-5, m.p. 68-70(degrees C) could be a terpene ketone.
Available to the general public.
Thesis (Master of Science in Pharmaceutical Chemistry)--University of the Philippines, 1980.
Keywords: Compositae--Compositions.; Vernonia patula; Terpenes